A Study of Serum PCT, LDH, IL-6, IL-1β, IL-10 after of PDCA and Enhanced Recovery After Surgery on Cesarean Section Patients: Serum PCT, LDH, IL-6, IL-1β, IL-10 after Cesarean - Chen, Liping; Xue, Lili (Journal of Medical Biochemistry, 2025)
Aim : Traditional perioperative care lacks continuity, prompting the use of PDCA (Plan-Do-Check-Act) and ERAS (Enhanced Recovery After Surgery) protocols to optimize recovery.This study examines the impact of combining PDCA and ERAS protocols on Serum PCT, LDH, IL-6, IL-1β, IL-10 ,postoperative recovery, pain, psychological well-being, and overall outcomes after cesarean section.Methods: In a prospective study, 120 CS patients were divided into an experimental group (OG) and a control group (CG). The OG received PDCA and ERAS-based care, including preoperative education, psychological counseling, multimodal analgesia, and tailored postoperative care. The CG received standard care. Key outcomes—pain (VAS), psychological status (SAS, SDS), recovery times, complications, satisfaction, and biomarkers (PCT, LDH, IL-6, IL-1β, IL-10)—were compared between groups.Results: The OG demonstrated significantly better outcomes than the CG in several areas. Pain levels at 4- and 72-hours post-surgery were lower in the OG. Psychological distress (SAS and SDS scores) was reduced, and recovery times (anal exhaust, first defecation, and ambulation) were shorter. The OG also had a lower incidence of complications and higher satisfaction scores. Biomarker analysis showed improved regulation of inflammation in the OG, with lower levels of pro-inflammatory markers (PCT, LDH, IL-6) and higher levels of anti-inflammatory cytokines (IL-10). These findings suggest a better overall recovery trajectory for patients in the OG.Conclusions: The integration of PDCA and ERAS protocols significantly enhances recovery following cesarean section. By improving pain management, psychological well-being, and reducing complications, these frameworks contribute to faster recovery and better overall patient outcomes. The study also highlights the potential of using inflammatory biomarkers as objective indicators of postoperative recovery. Despite the limitations of sample size and study design, these findings support the adoption of a more structured, patient-centered approach to cesarean section care.
Keywords: PCT, LDH, IL-6, IL-1β, IL-10, Cesarean section, PDCA cycle, ERAS protocols, postoperative recovery, pain management, psychological well-being, biomarkers, inflammation,